Psychological impact of the covid-19 pandemic on the operating room paramedical staff. (1st June 2022) - Hamada, H.; Soussi, M.; Chrigui, R.; Guellim, S.; Kahloul, M.; Naija, W.
Abstract : Introduction: the recent covid19 pandemic is not devoid of psychological risks on paramedical staff. Among them, those who work in the operating theaters are exposed to such risks. Objectives: to determine the perceived stress level and the psychological impact of COVID-19 on paramedics in the operating room. Methods: This is an observational, descriptive and analytical study carried out in the operating rooms of Sahloul University Hospital during a 3 month period. The data collection tool was a self-administered questionnaire composed of 5 main parts (socio-demographic characteristics, occupational characteristics, exposure to COVID-19, the Perceived Stress Scale (PSS) and the Hospital Anxiety and depression scale (HADS)). Results: 96 paramedical staff participated in our study. The average perceived stress score was significantly higher among anesthetists. 48% of participants had anxiety. Anesthetists had significantly higher anxiety scores (p = 0.001). 26.1% of participants had definite depression. Of those with definite depression, 35.3% were anesthetists (p = 0.028). Factors significantly associated with the occurrence of anxiety were: psychiatric history, increased workload, contact with a positive coronavirus patient in the operating room, and severe perceived stress. However, the factors significantly associated with the occurrence of depression were: initial training in the management of covid-19 patients, personal infection with SARS-COV2 and severe perceived stress. Conclusions: Covid-19 pandemic is causing significant symptoms of anxiety and depression among operation room staff. Primary and secondary prevention strategies must then be undertaken. Disclosure: No significant relationships.